ANALISI EFEKTIFITAS IKLAN PONDS WHITE BEAUTY DITELEVISI TERHADAP PEMBELIAN DI KOTA PONTIANAK - B11108033, YULIANA SEFTIANA (Jurnal Manajemen Update, 2013)
Advertising development is sparkling marked by the increasing of sorts of advertising media such as newspapers and magazines, electronic media such as television, radio and computer, outdoor media such as billboard and banners. One of the products which is quite often broadcasted on TV is Ponds. Ponds was first produced by a scientist Theron T in United States in 1846. This paper entitled An Analysis of the effectiveness of Ponds White Beauty advertisement on TV to the its sales in Pontianak. Using descriptive analysis method, this study examined the effectiveness of Ponds White Beauty advertisement on TV to the sales in Pontianak. Participants, female teenagers who use Ponds in Pontianak, completed the questionnaire as the prime data. The result of this study is to analyse the effectiveness of an advertisement through communicative approach by using EPIC model. This model measures the effectiveness of an advertisement from four (4) dimensions of values that is Empathy, Persuasion, Impact, and Communication. As the indicator of the analysis empathy asked two questions, persuasion with four questions, impact with two questions and communication with three questions. The result shows that the advertisement of Ponds White Beauty is quite effective. It is suggested that the advertisement being measured should be actual and still actively broadcasted on media such as electronics, printed, and so forth during the research. Keywords: An Analysis EPIC Model